Emerging Methods for Structural Analysis of Protein Aggregation - Khan, Eshan; K. Mishra, Subodh; Kumar, Amit (Protein and Peptide Letters, 2017)
Protein misfolding and aggregation is a key attribute of different neurodegenerative diseases. Misfolded and aggregated proteins are intrinsically disordered and rule out structure based drug design. The comprehensive characterization of misfolded proteins and associated aggregation pathway is prerequisite to develop therapeutics for neurodegenerative diseases caused due to the protein aggregation. Visible protein aggregates used to be the final stage during aggregation mechanism. The structural analysis of intermediate steps in such protein aggregates will help us to discern the conformational role and subsequently involved pathways. The structural analysis of protein aggregation using various biophysical methods may aid for improved therapeutics for protein misfolding and aggregation related neurodegenerative diseases. In this mini review, we have summarized different spectroscopic methods such as fluorescence spectroscopy, circular dichroism (CD), nuclear magnetic resonance (NMR) spectroscopy, Fourier transform infrared spectroscopy (FTIR), and Raman spectroscopy for structural analysis of protein aggregation. We believe that the understanding of invisible intermediate of misfolded proteins and the key steps involved during protein aggregation mechanisms may advance the therapeutic approaches for targeting neurological diseases that are caused due to misfolded proteins.
Keywords: fluorescence spectroscopy